Crisis nursery services and foster care prevention: An exploratory study. (February 2016) - Crampton, David; Yoon, Susan
Abstract: Objective: To examine whether receiving crisis nursery services reduces the chances of subsequent placement of children into foster care. Method: The study includes a sample of 322 children from the administrative data from a crisis nursery in Ohio. Generalized estimating equations analysis was conducted to assess the relationship between crisis nursery services (case management and parenting education) and subsequent foster care placement. Results: The generalized estimating equations analyses indicated that case management and parenting education provided from the crisis nursery were associated with reduced likelihood of subsequent foster care for children who were placed in the crisis nursery. Foster care placement during the previous 12 months and Caucasian race were also associated with higher odds of subsequent foster care placement. Conclusions: Crisis nursery services delivered with case management and parenting education may be an effecive intervention to reduce children's subsequent foster care placement. Highlights: Parental participation in case management and parenting education predicted lower odds of children's foster care placement Foster care placement during the previous 12 months predicted higher odds of children's subsequent foster care placement Caucasian children had higher odds of foster care placement than biracial children